A Study of Differential Impact of the Protracted National Conflict in Vavuniya District - Nanthakumaran, R.; Mangaleswaran, T.; Shanmugathasan, S. (Vavuniya Campus of the University of Jaffna, 2009)
This study focused on the differential impact of protracted conflict in general and especially on small business, trade links and cohesion among the conflict- affected community, examines the behavior of the villagers in the existing socioeconomic and cultural context and recommends measures for sustainable development of the community. The data were collected from three Divisional Secretariat (DS) Divisions (Vavuniya, Vavuniya South and Vengala Cheddikulam) in Vavuniya District. Three villages from each of the DS divisions were selected. A totally 120 respondents responded to the questionnaire. Focused group discussion and the key informant interviews were also conducted. Quantitative and qualitative analyses were conducted. Quantitative data were analyzed with the help of SPSS software package. Protracted national conflict has made an impact on the economy, social and human rights politics, practice of traditional culture, security and psychology of the people. It has caused death and disability to the people. The conflict has affected all communities in Vavuniya District. However, it has made differential impact on different communities. Tamil community has been disproportionately affected compared to other communities. Therefore, there is much to be done in cohesion building, which is very essential for sustainable development of conflict- affected people.
Keywords: Conflict; small business; trade link; social cohesion